Trust in Agent Societies 11th International Workshop, TRUST 2008, Estoril, Portugal, May 12 -13, 2008. Revised Selected and Invited Papers - Falcone, Rino; Barber, K. Suzanne; Sabater-Mir, Jordi; Singh, Munindar P. (Lecture Notes in Artificial Intelligence, 2008)
This book constitutes the thoroughly refereed post-workshop proceedings of the 11th International Workshop on Trust in Agent Societies, TRUST 2008, held in Estoril, Portugal, in the context of AAMAS 2008, the main international conference on autonomous agents and multi-agent systems. The 17 revised full papers presented were carefully reviewed and selected from numerous submissions; they are fully revised to incorporate reviewers' comments and discussions at the workshop. The volume is organized in ternary topical sections on theoretical and applicative aspects of trust (from a engineering, cognitive, computational, sociological point of view), on formal models in the field of applied logic and applied mathematics, and finally on models of reputation systems, theory-driven and empirically backed-up guidelines for designing reputation technologies, and analysis and discussion of existing reputation systems.